Pengembangan Media Pembelajaran Digital Berbasis Budaya Lokal Pada Mata Pelajaran Pai Di Sekolah Dasar - M. Hasan; Rafiuddin Rafiuddin; Nawir Rajadming; Syarifuddin Sahid (Jurnal PGSD Universitas Lamappapoleonro, 2026)
This study aims to analyze the development of digital learning media that integrates local culture into Islamic Religious Education (IRE) instruction in elementary schools through a literature review approach. This study stems from the phenomenon of the increasing use of digital technology in education, which has not been optimally accompanied by the strengthening of local cultural elements in the learning process. This situation results in learning that tends to lack context, meaning that the material presented is not fully connected to the students’ experiences and living environments. The method used in this study is library research, utilizing various relevant scientific sources, such as books, journal articles, conference proceedings, and other academic documents. Data collection was conducted through documentation techniques, while data analysis employed content analysis using a descriptive qualitative approach. The results of the study indicate that digital learning media based on local culture play a significant role in supporting the improvement of the quality of PAI learning in elementary schools. The integration of local cultural values into digital media can enhance the relevance of the material to students’ lives, deepen conceptual understanding, increase learning motivation, and strengthen character development and cultural identity. Additionally, the combination of digital technology and local culture in digital media